Implementing Business Model Canvas for Cibinong Science and Technology Park - Anang Hidayat; Tommy Hendrix; Mauludin Hidayat (Jurnal Bisnis Manajemen, 2018)
The purpose of this study is to discuss about the design of business models Cibinong Science and Technology Park (CSTP) based on the position of CSTP managed by government agencies should be subject to formal rules and regulations in force. CSTP predictable business model design can operate with more flexibility than the existing business model today. CSTP business model design is expected to provide value not only to entrepreneurs (tenant), but also for the environment CSTP in order to manage the business with a healthy and sustainable. The method used in this research is descriptive approach by utilizing the framework Business Model Canvas (BMC) which is used to assess some business model variables at the Science and Technology Park (STP). The analysis shows that the management team CSTP have to revisit the structure of employment and work organization and the design of the operation, and CSTP can identify the target and the type of services or products needed. Further, CSTP should make a proposal which includes how to generate and deliver value, an important resource that CSTP have and what key activities should be developed for the future.